2021
DOI: 10.1016/j.foodhyd.2021.106660
|View full text |Cite
|
Sign up to set email alerts
|

Saliva matters: Reviewing the role of saliva in the rheology and tribology of liquid and semisolid foods. Relation to in-mouth perception

Abstract: In recent years, the dynamic aspects of the oral perception of food have increasingly been taken into account in food texture characterization. At the same time, the experimental settings of instrumental measurements have also been emulating "oral contexts" more closely. The aspects related to in-mouth handling that have been incorporated into food studies include using saliva as a key material. Semisolid (or liquid) food does not usually need mastication but undergoes more subtle processes involving the tongu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 106 publications
(113 reference statements)
2
14
0
Order By: Relevance
“…It has been previously reported that harder foods, for example, can help prolong chewing and taste, which can be positive for patients with anosmia and ageusia ( de Graaf, 2020 ; Joyner, 2018 ; Laguna, Fiszman, & Tarrega, 2021 ). In addition, these foods increase chewing, reduce overeating rates and promote satiety ( Bolhuis & Forde, 2020 ; Ohkuma et al, 2015 ; Robinson et al, 2014 ).…”
Section: Recreating Sensory Texture For Patients With Anosmia and Ageusiamentioning
confidence: 99%
“…It has been previously reported that harder foods, for example, can help prolong chewing and taste, which can be positive for patients with anosmia and ageusia ( de Graaf, 2020 ; Joyner, 2018 ; Laguna, Fiszman, & Tarrega, 2021 ). In addition, these foods increase chewing, reduce overeating rates and promote satiety ( Bolhuis & Forde, 2020 ; Ohkuma et al, 2015 ; Robinson et al, 2014 ).…”
Section: Recreating Sensory Texture For Patients With Anosmia and Ageusiamentioning
confidence: 99%
“…Saliva present in the oral cavity is recognized as the first liquid that interacts with materials or compounds coming from the external environment [1,2]. Furthermore, its presence is crucial in several basic food processes, such as lubrication, digestion and solubilization in the oral environment [2,3]. Saliva is predominantly water (99%); however, there is a high range of proteins, different minerals, dead cells and a large amount of bacteria associated with the composition [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Gelatinized starch granules are therefore rapidly hydrolyzed by salivary α‐amylase into oligosaccharides such as maltose, maltotriose, maltotetraose, etc (Hoebler et al, 1998). This structural breakdown may modify the bolus rheology, influence texture perception, aroma release, and swallowing safety (Laguna, Fiszman, & Tarrega, 2021; Vallons, Oudhuis, Helmens, & Kistemaker, 2015; de Wijk, Janssen, & Prinz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…texture perception, aroma release, and swallowing safety (Laguna, Fiszman, & Tarrega, 2021;Vallons, Oudhuis, Helmens, & Kistemaker, 2015;de Wijk, Janssen, & Prinz, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation